Probabilistic inference of the genetic architecture underlying functional enrichment of complex traits - Marion Patxot (Nature Portfolio, 2021)
Improving inference in large-scale genetic data linked to electronic medical record data requires the development of novel computationally efficient regression methods. Here, the authors develop a Bayesian approach for association analyses to improve SNP-heritability estimation, discovery, fine-mapping and genomic prediction.